Contribution of pharmaceutical drugs of dependence to the incidence of neonatal abstinence syndrome in Western Australia between 2003 and 2018. Issue 5 (4th April 2022) - Kelty, Erin A.; Cumming, Craig N.; Preen, David B.
Abstract: Study objective: The aim of this study was to examine the incidence of neonatal abstinence syndrome (NAS) in Western Australia (WA) and estimate the contribution of pharmaceutical drugs of dependence (PDD) to NAS. Design: A population‐based birth cohort study. Data source: Neonates were identified through the Midwives Notification Scheme. Linked medication dispensing and hospital records were used to identify exposure to PDD and NAS diagnosis. Patients: All live born neonates born in WA between 2003 and 2018. Measurements: The incidence of NAS and percentage of NAS diagnoses associated with exposure to PDD. Main results: During the study period, the incidence of NAS did not significantly change (annual percentage change (APC): 0.6, 95%CI: −1.3, 2.6), with 3.8 neonates per 1, 000 live births diagnosed with NAS. PDD were dispensed to 41.4% of mothers of neonates with NAS, with PDD used to treat opioid use disorders the most commonly prescribed (35.2% of neonates with NAS), while opioid PDD used in the treatment of pain contributed to 5.2% of NAS cases. Non‐opioid PDD contributed to 1.7% of cases of NAS. The incidence of NAS associated with the use of opioids used to treat opioid use disorders (OUD) decreased over the study period (APC: −6.5, 95%CI: −9.5, −3.4), while NAS associated with opioids used to treat pain remained stable (APC: −2.7, 95%CI: −7.1, 1.9). Conclusion: The incidence of neonatal abstinence syndrome in WA remained stable from 2003 to 2018. Medications used to treat opioid use disorders were a substantial driver of NAS, although NAS associated with these medications has declined over time.